The Hand and Glove Puppet in Teaching English as Foreign Language: Speaking Skill for Compliment - Maria Ramasari; Windi Virgia (ELT-Lectura, 2019)
The objective of this research was to find out whether or not it was significantly difference achievement between the tenth grade students of MA Negeri 1 (Model) Lubuklinggau who were taught speaking by using Hand and Glove Puppets and those who were not taught speaking by using Hand and Glove Puppets. The researcher used quasi-experimental research. The sample of this research was taken by using cluster random sampling with 30 students in the experimental group, and 30 students in the control group taken from two classes of the tenth grade students of MA Negeri 1 (Model) Lubuklinggau. Based on the result of the data analysis there were three major findings namely: (1) the students’ score in the pre-test, (2) the students’ score in the post-test, and (3) the result of paired T-Test calculation. The mean score in the pre-test of the Experimental group was 63.88 and the mean score in the pre-test of the Control group was 49.77. While, the mean score in the post-test of the Experimental group was 72.44 and the mean score in the post-test of the Control group was 56.21 The result of paired t-test calculation shows that tobtained was 7.70 in the pre-test of the experimental and control group and 8.91 in the post-test of the experimental and control group. It was higher than 2.045 as the critical value of the ttable of degree of freedom 29 with 0.05 significant level for two-tailed test. So, the null hypotheses was rejected and the alternative hypotheses was accepted. It meant that it was effective to teaching speaking by using Hand and Glove Puppets to the tenth grade students of MA Negeri 1 (Model) Lubuklinggau.